CBDC and banks: Disintermediating fast and slow - Rhys Bidder; Timothy P. Jackson; Matthias Rottner (Deutsche Bundesbank, 2024)
We examine the impact of central bank digital currency (CBDC) on banks and the broader economy - drawing on novel survey evidence and using a structural macroeconomic model with endogenous bank runs. A substantial share of German respondents would include CBDCs in their portfolio in normal times - replacing, in part, commercial bank deposits. This is hypothetical evidence for 'slow' disintermediation of the banking system. During periods of banking distress, households' willingness to shift to CBDC is even larger, implying a risk of 'fast' disintermediation. Our structural model captures both phenomena and allows for policy prescriptions. We calibrate to the Euro area and then introduce CBDC, exploiting our survey to parameterize its demand. We find two contrasting effects of CBDC on financial stability. 'Slow' disintermediation shrinks a run-prone banking system with positive welfare effects. But the ability of CBDC to offer safety at scale makes bank-runs more likely. For reasonable calibrations, this second 'fast disintermediation' effect dominates and the introduction of CBDC decreases financial stability and welfare. However, complementing CBDC with a holding limit or pegging remuneration to policy rates can reverse these results such that CBDC is welfare improving. Such policies retain the gains of increased stability arising from 'slow' disintermediation while limiting the downsides of 'fast' disintermediation.
Keywords: 330